Regulators of stream ecosystem recovery from disturbance - Murdock, Justin N. (Kansas State University, 2008)
Streams exist in a state of dynamic equilibrium with frequent floods and drought. The frequency and intensity of stream disturbances are projected to increase with greater water withdrawal for agriculture and biofuel production, watershed development, and altered climate. Changes in the hydrologic regime may alter stream ecosystems. I studied how stream communities return after disturbances and how nutrients, consumers, and substrata heterogeneity influence recovery trajectories. Large consumers were excluded from pools following a severe drought to assess how community structure and function returned in their absence. Large consumers reduced algal biomass, primary productivity, and nutrient uptake rates, and delayed macroinvertebrate recolonization. However, grazer effects were temporary and their influence weakened after five weeks. In a second experiment, I assessed the relative influence of grazer density and nutrient loadings on algal recovery from flood. Nutrients had a stronger effect on recovery than grazers, but the strength of each varied temporally. Grazer control decreased and nutrient control increased over time. A third experiment addressed the physical properties of stream substrata on algal development. The relationship among algal accumulation and substrata surface topography was assessed by growing algae on substrata with varying orientation and roughness. Total algal biomass decreased on surfaces with angles > 45 degrees, and peaked at an intermediate roughness (pit depth of [similar to]17 [Mu]m). Rougher surfaces collected more tightly attached (grazer resistant) forms and less loosely attached (grazer susceptible) forms. Individual algal forms responded differently to grazing pressure, nutrient availability, and surface features. I developed a method using Fourier-transform infrared microspectroscopy to measure single-cell physiological responses in benthic algae. Nutrients and consumers were strong regulators of ecosystem succession following disturbance, but nutrient influence was stronger. The influence of nutrients and consumers were context dependent, and changed over the course of recovery. Rougher surfaces increase algal growth and shifted algal assemblages to more grazer resistant forms, which may decrease the influence of large consumers on stream function. Altering the severity and frequency of disturbances can change the trajectory of stream recovery and ultimately change community composition and stream metabolic activity, which may alter ecosystem services such as water purification and recreation.
Keywords: Stream; Flood; Drought; Algae; Substrata; Infrared spectroscopy; Biology, Ecology (0329)